Quinazoline and quinazolinone as important medicinal scaffolds: a comparative patent review (2011–2016). (3rd April 2018) - Hameed, Abdul; Al-Rashida, Mariya; Uroos, Maliha; Ali, Syed Abid; Arshia,; Ishtiaq, Marium; Khan, Khalid Mohammed
ABSTRACT: Introduction : Quinazoline and quinazolinone scaffolds represent an important class of biologically active nitrogen heterocyclic compounds. A variety of marketed drugs are based on these moieties. A diverse range of molecules with quinazoline/quinazolinone moieties have been reported to exhibit broad spectrum of biological activities. Area covered : This review covers recent efforts in the synthesis and biological screening of quinazoline/quinazolinone based compounds from 2011–2016. Expert opinion : Quinazoline and quinazolinones represent a diverse class of biologically active nitrogen heterocyclic compounds with immense therapeutic potential. Their ease of synthetic accessibility, and flexibility in structural modifications and functionalization further adds to their appeal in medicinal chemistry. A number of currently available drugs are based on quinazoline/quinazolinone scaffold. It is interesting to note that, among the recent patents available, a lot of them focus on the promising anticancer activity of quinazoline and quinazolinone containing compounds. However their biological activity is certainly not limited to anticancer only, they are also known to elicit a number of other biological and physiological effects in vitro and in vivo respectively. The interest in quinazolines and quinazolinones is ever growing, since they offer a fairly diverse chemical space for exploration of medicinal potential.